2020
DOI: 10.1021/acs.jpcc.0c04252
|View full text |Cite
|
Sign up to set email alerts
|

Polaron-Induced Deep Defect Levels in Brookite TiO2: A Many-Body Green’s Function Theory Study

Abstract: Brookite is now recognized as an active phase of TiO 2 which exhibits superior activities compared with anatase and rutile in some photocatalytic reactions. However, there is still little research and knowledge on its electron properties as well as the crucial role of defects in brookite. Using the ab initio many-body Green's function theory, we examined the quasiparticle structures of defects, including oxygen vacancies, Ti interstitials, and hydroxyl groups, in the bulk and the (210) surface of brookite. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…30 Theoretical calculations predicted electron-trap energies of 0−0.2 and 0.8−1 eV for anatase and rutile, 38 respectively, and it was shown that brookite has a shallow trap and a deep trap, corresponding to 0.3 and 0.7 eV of photon energy below the bottom of the conduction band. 39 Considering our results and results of theoretical calculations, it is thought that the process by which photogenerated electrons accumulate in TiO 2 particles is largely determined by the energy level of trapping sites, depending on the crystal structure. It has been reported that most of the photogenerated electrons in rutile are deeply trapped at defective sites within a few picoseconds and that free electrons in brookite are captured at defective sites within a few picoseconds.…”
Section: ■ Results and Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…30 Theoretical calculations predicted electron-trap energies of 0−0.2 and 0.8−1 eV for anatase and rutile, 38 respectively, and it was shown that brookite has a shallow trap and a deep trap, corresponding to 0.3 and 0.7 eV of photon energy below the bottom of the conduction band. 39 Considering our results and results of theoretical calculations, it is thought that the process by which photogenerated electrons accumulate in TiO 2 particles is largely determined by the energy level of trapping sites, depending on the crystal structure. It has been reported that most of the photogenerated electrons in rutile are deeply trapped at defective sites within a few picoseconds and that free electrons in brookite are captured at defective sites within a few picoseconds.…”
Section: ■ Results and Discussionmentioning
confidence: 62%
“…In our previous study, we revealed that the Ti 3+ levels of anatase, rutile, and brookite TiO 2 powders lie mainly at 0.11–0.28, 0.97–1.0, and 1.1 eV, respectively, below the bottom of the conduction band . Theoretical calculations predicted electron-trap energies of 0–0.2 and 0.8–1 eV for anatase and rutile, respectively, and it was shown that brookite has a shallow trap and a deep trap, corresponding to 0.3 and 0.7 eV of photon energy below the bottom of the conduction band . Considering our results and results of theoretical calculations, it is thought that the process by which photogenerated electrons accumulate in TiO 2 particles is largely determined by the energy level of trapping sites, depending on the crystal structure.…”
Section: Results and Discussionmentioning
confidence: 95%
“…Some of them have been reviewed recently . The most studied systems among these GW+BSE calculations include point defects in SiC, diamond, and hexagonal boron nitride, which serve as potential candidates as the single-photon source for optoelectronic devices, quantum information and quantum computing, and point defects in TiO 2 , which have wide applications in catalysis and solar cells.…”
Section: Theorymentioning
confidence: 99%
“…Ref ’s GW analysis indicated that the bond formed between the Ti interstitial and a Ti lattice atom is the source of the defect state, a finding that is in contrast to DFT + U and HSE calculations. Zhang et al used the same level of theory to study defects in Brookite TiO 2 and found that for a variety of likely defects, in-gap states ranging from 0.5–1.0 eV from the conduction band minimum are introduced both in the bulk and surface, which qualitatively agrees with experimental expectation. In contrast, LDA+U with a U value of 5 eV predicted defect states too deep in the gap.…”
Section: Benchmark Studies Of Mbpt For Point Defects In Materialsmentioning
confidence: 99%